2019
DOI: 10.1097/j.pain.0000000000001519
|View full text |Cite
|
Sign up to set email alerts
|

The medial temporal lobe in nociception: a meta-analytic and functional connectivity study

Abstract: processing. Of importance, there has yet to be a formal investigation of the spatial consistency of MTL activations in healthy participants during experimental pain.In addition to studies in healthy participants, extant evidence indicates aberrant MTL activity in various chronic pain conditions [56,104,108]. Recent evidence in patients with back pain suggests that the transition from subacute to chronic pain may be mediated by MTL structures [134]. Specifically, reduced MTL resting state functional connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 149 publications
(133 reference statements)
4
22
0
Order By: Relevance
“…A novelty of this study is the finding that patients with BMS showed a statistically significant difference in the WMCs of temporal lobe structures compared with age-matched healthy subjects (Figure 3); probably because the temporal lobe has a key role in pain and mood modulation and exhibits an abnormal activity in chronic pain (Galton et al, 2001;Ayoub et al, 2019). In addition, the presence of confluent WMCs in this brain area has been considered as the predictive of progressive medial temporal lobe atrophy, frequently detected in AD, and therefore it might be a meaningful measure of brain disease progression and an additional risk factor (Galton et al, 2001;Ayoub et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…A novelty of this study is the finding that patients with BMS showed a statistically significant difference in the WMCs of temporal lobe structures compared with age-matched healthy subjects (Figure 3); probably because the temporal lobe has a key role in pain and mood modulation and exhibits an abnormal activity in chronic pain (Galton et al, 2001;Ayoub et al, 2019). In addition, the presence of confluent WMCs in this brain area has been considered as the predictive of progressive medial temporal lobe atrophy, frequently detected in AD, and therefore it might be a meaningful measure of brain disease progression and an additional risk factor (Galton et al, 2001;Ayoub et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…In healthy participants, consistent activation in the right anterior hippocampus, parahippocampal gyrus, and amygdala was found. In chronic pain patients, consistently less activation in patients' anterior hippocampus was elucidated compared with healthy participants (Ayoub et al, 2019). In a systematic review of MRI and fMRI studies exploring structural and functional brain changes in chronic low back pain patients, it was found that only 3 of 10 functional MRI studies observed significant differences during noxious stimulation between pain patients and control groups whereas 13 of 16 studies observed significant brain activation differences between pain patients and controls during various external tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal lobe is generally responsible for establishing long-term memory, cognitive and emotional functions, and auditory processing [ 23 ]. However, several neuroimaging studies have reported altered activation within this region [ 24 , 25 , 26 ]. In patients with chronic low back pain, the anterior hippocampus, a part of the medial temporal lobe, showed significantly lower levels of activity and functional connectivity than the medial prefrontal cortex [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several neuroimaging studies have reported altered activation within this region [ 24 , 25 , 26 ]. In patients with chronic low back pain, the anterior hippocampus, a part of the medial temporal lobe, showed significantly lower levels of activity and functional connectivity than the medial prefrontal cortex [ 26 ]. The anterior hippocampus is involved in mood-related functions and psychological modulation, likely through interactions with the amygdala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation